Analisis Kebijakan Kepala Sekolah Dalam Pelaksanaan Pembelajaran Daring - Setiyadi, Bradley; Firman; Saputri, Cahyani (Kelola: Jurnal Manajemen Pendidikan, 2023)
This study examined the principal's policy and the implementation of online learning during the Covid-19 pandemic at SDN 206/X Pandan Jaya. Employing a qualitative descriptive approach with phenomenological research, data was collected through observations, interviews, and document analysis. Data analysis  used are data reduction, data presentation, and conclusion drawing. The results showed that: (1) The principal of SDN 206/X Pandan Jaya has established a policy of implementing online learning with and following up on a Surat Edaran Menteri Pendidikan dan Kebudayaan Nomor 4 Tahun 2020 concerning the implementation of distance learning, principals involve educators in making decisions, school principals encouraging the creativity of educators in teaching in the midst of a pandemic, the final results obtained by students are almost the same as offline learning outcomes or outside the network, (2) the advantages of implementing online learning are: students get easier learning through the help and monitoring from parents and gain experience building cooperation in a group, (3) lack of implementation of online learning namely limited facilities and internet signal instability.